The relationship between efforts for tax learning, awareness of tax laws, understanding of tax laws and tax compliance behaviour among salaried taxpayers in Mogadishu-Somalia - Ali, Zakarie Ahmednor (2017)
This study investigates the relationship between tax education dimensions and tax compliance behaviour among salaried taxpayers in Mogadishu, Somalia. This study is motivated by low tax compliance and low tax education in Somalia. Specifically, the objectives of this study were to examine the relationships between efforts for tax learning, awareness of tax laws and understanding of tax laws; and tax compliance behaviour among salaried taxpayers in Mogadishu, Somalia. To achieve the research objectives, primary data were collected through administrating survey questionnaires to salaried taxpayers in Mogadishu, Somalia. The data were analysed using multiple regression analysis. The findings of the study indicate that efforts for tax learning had a negative and significant relationship with tax compliance behaviour. on the other hand, the awareness of tax laws and understanding of tax laws had a positive and insignificant relationship with tax compliance behaviour. efforts for tax learning contributes the most towards tax compliance behaviour. therefore, the policy makers in somalia should focus more on the most important contributing factor, i.e. efforts for tax learning, to enhance tax compliance and ultimately mitigate the problem of noncompliance in Somalia.